A locação via Airbnb nas dinâmicas de ocupação imobiliária residencial da orla marítima de Aracaju - Trindade, João Vítor Araujo (Universidade Federal de São Carlos, 2025)
This dissertation proposes a contribution to the understanding of the impacts resulting from the actions of financialized agents guided by rentier capitalism on real estate dynamics and how they transform the urban space, especially after the digitalization process. In this context, the focus of the study is Airbnb, a global Short-Term Rental platform, exponent of the sharing economy and associated with a variety of urban phenomena such as gentrification and touristification, thus altering the dynamics of cities through tourism. The observation of the platform was related to its operations in the city of Aracaju, capital of the state of Sergipe, where processes of association between the State and real estate capital guided local urban development. The relationship between the real estate and tourism sectors in the housing production and occupation in the neighborhoods along the Aracaju coastline is evident, including aspects of segregation and environmental appropriation. In this sense, the work aims to analyze the relationship of mutual influence between the offer of accommodations of the platform and the real estate dynamics of the city. It is contended that Airbnb promotes the vacancy and idleness of housing units, repurposing them for functions other than housing. This is purportedly done to increase their rental value and favor the neoliberal logic of individualistic entrepreneurship. Aracaju, being a city outside the major economic centers of national capitalism and not part of the traditional tourist circuit, has shown low levels of financial activity within the dynamics of Airbnb in the city. On the other hand, the real estate dynamics in the occupation of coastal neighborhoods demonstrate a tendency towards a rentier appropriation of the coastal landscape, and the insertion of Airbnb in this system deepens the relationships already established. The data collected on the platform's activity indicate a relatively high presence of accommodations when compared to similar cities in Brazil. The high proportion of entire spaces stands out, as well as the relevance of professional hosts in the local offer. Thus, the dominance of a rentier logic of appropriation of space, landscapes and the environment is validated.
Airbnb rentals in the dynamics of residential real estate occupation on the Aracaju seafront
Keywords: Rentismo; Financeirização imobiliária; Aracaju; Dinâmicas imobiliárias; Economia de compartilhamento; Rentierism; Housing financialization; Real estate dynamics; Sharing economy; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ESTUDOS DA HABITACAO